STEM Pathway and College Progression: The Link Between Engineering CTE and Postsecondary Outcomes for Students With Learning Disabilities - Jay Plasman; Desmond Myles
Despite growing calls to increase diversity in science, technology, engineering, and mathematics (STEM) fields, students with learning disabilities (SWLDs) remain underrepresented in STEM at the postsecondary level. Considering this call for increased diversity as a means to expand and strengthen STEM success, we used the High School Longitudinal Study of 2009 to explore how participation in engineering career and technical education (E-CTE) links to postsecondary educational outcomes for SWLDs. Particularly, we examined how E-CTE participation relates to postsecondary remedial course taking, enrollment in a 4-year postsecondary institution, and declaration of a STEM major. Results from school fixed-effects estimations suggest that each credit of E-CTE earned is associated with fewer remedial college courses, a higher likelihood of enrolling in a 4-year as opposed to sub-baccalaureate institution, and increased odds of declaring a STEM major. To conclude, we discuss the implications of our findings for both policymakers and practitioners.